Prinsip Pendidikan Islam dalam Penerapan Aqiqah dan Tasmiah - Munir, Misbahul; Rosadi, Khumaini; Minarsih (NABAWI: Jurnal Penelitian Pendidikan Islam, 2023)
Usually, two acts of worship—tasmiyah and aqiqah—are carried out on the same day, which is the seventh day following a child's birth. When someone is gifted a kid by Allah SWT, they have several obligations to complete, such as performing tasmiyah and aqiqah. It is crucial to take good care of the aqiqah on the seventh day after birth. There is a birthday count. Like the Hajj, cutting one's hair after the aqiqah killing is sunnah. Tasmiyah is also observed on the seventh day. It is Sunnah to give alms equivalent to the weight of a haircut. The purpose of this study is to identify the principles that underpin tasmiah (Islamic education) and Aqiqah implementation. This study makes use of qualitative research methods. Aqiqah is a way for parents to show their love for their child and provide them their first education. The Jahiliyah used to also conduct aqiqah. The Prophet replaced this with the Islamic aqiqah ritual, which had educational significance, in ancient times. This study employs a qualitative methodology, gathering data from relevant literature through the use of a library research design.  Finding the fundamental ideas of tasmiah, or Islamic education, and aqiqah practice is the aim of this research.